Effect of sloping bottom on river plume dynamics on a laboratory-scale rotating table - Yuan, Yeping; Tan, Xinyu; Lin, Ying-Tien (Frontiers in Marine Science, 2023)
In nature, plumes usually enter the coastal ocean after they leave the estuary, and most of them interact with the continental shelf slope. To understand plume dynamics, laboratory experiments were carried out on a rotating table to simulate the evolution of plumes over a sloping bottom. We modified reduced gravity g’, Coriolis parameter f, and shelf slope α to study their impacts on plume characteristics and freshwater fate, and used the optical thickness method to obtain the depth field. We found that with the increasing g’ or decreasing f, plume maximum depth hmax decreases and plume maximum width Wmax increases. We proposed a method to determine plume types based on their attachment to the shelf slope: when PCN (plume classification number) > 1.6, the plume is bottom-attached; when PCN< 1.6, the plume is surface-advected. In addition, we found the bulge will become unstable when BIN (bulge instability number)< 0.8. Our analysis shows that the sloping bottom is the most significant factor determining the ratio of freshwater accumulated in the bulge over transported with coastal currents. Generally, bottom-attached plume trapped near the coast inhibits offshore freshwater transport and promotes coastal current transport, while baroclinic instability tends to produce a large cyclonic vortex over a gentle slope which strongly enhances the offshore transport.